FENOMENA TRASH-TALKING ANTAR PEMAIN GAME ONLINE MOBILE LEGENDS: BANG BANG (STUDI KASUS MAHASISWA ILMU KOMUNIKASI UIN SUMATERA UTARA) - Dean Marcella; Hasan Sazali (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Game Mobile Legends: Bang Bang is one of the most popular online games in Indonesia. One thing that is popular in the game is the trash-talking behavior. This research appears to find the meaning of trash-talking in the online game Mobile Legends. Using a qualitative-descriptive research method by finding data sources using the interview method with 5 informants who were determined by the purposive sampling method with the conditions that they were Communication Science students at UIN North Sumatra, active players in the Mobile Legends game: Bang Bang and were at epic levels/ranks. The analysis technique uses equivalent analysis. The results of the study show that there are 6 forms of trash-talking categories, namely: 1). Intelligence, including: Stupid, Stupid, Stupid, Paok, Use Your Brain, Blog/Impossible, and Remove ML. 2). Disgusting animals, including: Dogs, Asu, and Anjrit 3). Sexuality, including: Kimbek 4). Status, including: Yteam 5). Physical, including: Blind Map and 6). General includes: Bastard, Lol, and Jancok . Some of the things that cause them to issue trash-talking words are getting team members with very bad games, getting lost, and players who are AFK (Away From Keyboard) or leave the game during the game.